Enriching research attachment with Science, Culture and Friendship / Associate Prof. Dr Lim Siong Meng and Prof. Dr. Kalavathy Ramasamy - Lim, Siong Meng; Ramasamy, Kalavathy (Faculty of Pharmacy, 2023)
As part of the effort in inspiring young minds to pursue research, researchers at the Collaborative Drug Discovery Research (CDDR) group have been actively hosting local and international students (Indonesia, Pakistan and Spain) for short research attachment or research stint since 2014. Recently, the research group has had the privilege to host two pharmacy students from France, Claudiane Elina Tiffany Lequertier (Université Paris-Saclay) and Manon Marie Agathe Rampal (Université de Rennes), for a one-month (31st of July 2023 – 25th August 2023) research attachment under the Student Exchange Programme (SEP) organised by the International Pharmaceutical Students’ Federation (IPSF) in collaboration with the Malaysian Pharmacy Students’ Association (MyPSA). Their research activities (Figure 1) revolved around a simple project entitled “Antimicrobial and wound healing effects of postbiotics derived from lactic acid bacteria in vitro”, which was designed to expose them to various cell culture techniques, Sulforhodamine B and scratch assays. To provide them with a full research experience, we also guided them in terms of research logbook maintenance, data analysis, and interpretation as well as report writing.